2017
DOI: 10.1186/s13148-016-0307-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of DNA methylation in panic disorder

Abstract: BackgroundPanic disorder (PD) is considered to be a multifactorial disorder emerging from interactions among multiple genetic and environmental factors. To date, although genetic studies reported several susceptibility genes with PD, few of them were replicated and the pathogenesis of PD remains to be clarified. Epigenetics is considered to play an important role in etiology of complex traits and diseases, and DNA methylation is one of the major forms of epigenetic modifications. In this study, we performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 70 publications
1
43
2
2
Order By: Relevance
“…Notably, the significant changes in DNA methylation presented here are small with less than 1% difference (0.08%) but replicable. While the functional relevance of such small changes is debatable, these effect sizes are in line with other EWAS in psychiatry, including the recent small Japanese EWAS in PD 22 , where 40 significant CpGs with overall low methylation (mostly under 0.05%) differences have been detected. Sex-specific associations were not reported, most likely because of the small sample size.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, the significant changes in DNA methylation presented here are small with less than 1% difference (0.08%) but replicable. While the functional relevance of such small changes is debatable, these effect sizes are in line with other EWAS in psychiatry, including the recent small Japanese EWAS in PD 22 , where 40 significant CpGs with overall low methylation (mostly under 0.05%) differences have been detected. Sex-specific associations were not reported, most likely because of the small sample size.…”
Section: Discussionsupporting
confidence: 83%
“…To date, a few studies have investigated differences in DNA methylation in candidate genes in PD 5 , 18 21 . Recently, one epigenome-wide study of DNA methylation in a relatively small Japanese PD case-control sample (48 patients vs. 48 controls) detected significant associations at 40 sites with overall small methylation differences 22 . So far, studies in the European population are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the first two epigenome-wide association studies (EWAS) were published. Shimada-Sugimoto et al (2017) found 40 CpG sites that were significantly associated with PD. Most of them were hypomethylated and pathway analysis revealed genes in epidermis development, cell cycle regulation, and lymphocyte activation.…”
Section: From Laboratory To Real-life Assessmentmentioning
confidence: 99%
“…Methylation patterns are known to vary across cell types, where they contribute to the maintenance of cellular identities and to the response to environmental perturbations through the regulation of gene expression (Rakyan et al, 2008;Lister et al, 2009). In the brain, DNA methylation status has been associated with its structure and function (Wheater et al, 2020) and aberrations in methylation profiles, with sub-regional and cell-type specificity (Rizzardi et al, 2019) have been associated with many forms of mental illness (Grayson and Guidotti, 2013;Shimada-Sugimoto et al, 2017;Liu et al, 2018;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%